Farmers participatory evaluation of bread wheat varieties through seed producer cooperatives: evidence from Ethiopia - Dawit Tsegaye Sisay; Getnet Sharie; Belayneh Getnet; Anteneh Demissie; Rebeka Gebretsadik; Tadesse Dessalegn; Andrea Ruediger; Dessalegn Molla; Sebsebe Zewde; Cherinet Alem Gesesse; Eshete Abebe (Discover Agriculture, 2024)
Abstract The limited engagement of farmers and their community agents in the process of variety development and evaluation is one of the main factors for lower rates of variety adoption, which resulted in lower crop productivity. Participatory bread wheat variety evaluation was jointly conducted by breeders, members of seed producer cooperative (SPC) and local experts with the objectives to identify farmers’ selection criteria, to assess farmers’ preferred varieties and to increase the SPC’s variety portfolios. Twelve released bread wheat varieties were evaluated during 2019 cropping season at Sekela district of Amhara region, Ethiopia. Pair-wise ranking was used to identify farmers’ selection criteria and direct matrix ranking to prioritize those selected criteria. Varieties were planted in two sets with and without lime application. Grain yield, followed by earliness, disease tolerance, and tillering capacity, was identified the first preferred criterion by farmers. The mean values showed that higher yield was recorded with the lime application compared to no lime application. Lemu (6.4 t/ha), Alidoro (6.3 t/ha), Dambal (6.3 t/ha), Obora (6.1 t/ha) and Liben (6.1 t/ha) had greater yield with lime application. The t-test results indicated that significant difference between with and without liming for the number of tillers per plant, spike length per plant, plant height, 1000 seed weight, and hectoliter weight, but non-significant difference for grain yield. The selected varieties should be included in the production plan of the cooperatives for large scale production to increase the variety portfolios and to address the demand of the farming community.